Changes in the incidence and overall survival of patients with myeloproliferative neoplasms between 2002 and 2016 in the United States. Issue 3 (23rd February 2022) - Verstovsek, Srdan; Yu, Jingbo; Scherber, Robyn M.; Verma, Sumit; Dieyi, Christopher; Chen, Chien-Cheng; Parasuraman, Shreekant
Abstract: This analysis examined trends in incidence and survival among US adults with myeloproliferative neoplasms, including essential thrombocythemia (ET; n = 14, 676), polycythemia vera (PV; n = 15, 141), and primary myelofibrosis (PMF; n = 4214), using Surveillance, Epidemiology, and End User Results (SEER) data (SEER 18; 2002–2016). Incidence and survival rates over the study period and by diagnosis year (per 5-year time frames: 2002–2006; 2007–2011; 2012–2016) were assessed. The overall incidence rates (95% CI) were 1.55 (1.52–1.57) for ET, 1.57 (1.55–1.60) for PV, and 0.44 (0.43–0.45) per 100, 000 person-years for PMF, with rising ET incidence. Five-year mortality over the study period was 19.2%, 19.0%, and 51.0% for ET, PV, and PMF, respectively. Improved survival over time was observed for PV and PMF, but not for ET. These findings highlight the need for effective ET therapies, as ET incidence has risen without concurrent improvements in survival over the past 2 decades.